Gut-Based Strategies to Reduce Postprandial Glycaemia in Type 2 Diabetes - Kamruzzaman, Md; Horowitz, Michael; Jones, Karen L.; Marathe, Chinmay S. (Frontiers in Endocrinology, 2021)
Postprandial glycemic control is an important target for optimal type 2 diabetes management, but is often difficult to achieve. The gastrointestinal tract plays a major role in modulating postprandial glycaemia in both health and diabetes. The various strategies that have been proposed to modulate gastrointestinal function, particularly by slowing gastric emptying and/or stimulating incretin hormone GLP-1, are summarized in this review.